Fernando Leal Carretero (Ed. & Trans.). (2015). Argumentación y pragma-dialéctica (2017)
The Pragma-Dialectical approach to argumentation has, since its very beginnings, conceived of itself as a collaborative, interdisciplinary project, maintained and enriched by the active exchange Frans van Eemeren has constantly held and promoted with scholars from all over the world. The Hispanic academic community, in Europe as well as in the Americas, has not been the exception. This 632- page volume, selected, edited and translated by Fernando Leal Carretero (Centro Universitario de Ciencias Sociales y Humanidades, University of Guadalajara), intends not only to portray for the Hispanic audience the evolution and the state of the art in Pragma-Dialectical theory – as accounted for by its very leading figure – but also, and indeed quite importantly, the distinctive reception and contribution of Hispanic scholars to this ongoing research program.